Impact of Response Rates on Overall Survival Following Chemoradiotherapy with or Without Surgery in Esophageal Cancer - Kimia Çepni; Tuğçe Hilal Uçgun; Merve Şam Özdemir; Sümeyye Nur Aydın; Bahar Çepni; Huriye Şenay Kızıltan (Cerrahpaşa Medical Journal, 2026)
Objective: Neoadjuvant chemoradiotherapy (NACRT) plays an important role in the treatment of esophageal cancer. Current studies show that increased pathological response and R0-resection rates positively affect treatment outcomes. This study aimed to evaluate the clinical outcomes of patients who received NACRT with or without surgery. Methods: In this study, 72 patients diagnosed with esophageal cancer who underwent NACRT, with or without subsequent surgery, were retrospectively analyzed. Radiotherapy (RT) fields were defined based on the primary tumor location, and the median RT dose was 50.4 Gy (range: 41.4–54 Gy). The patients received a chemotherapy regimen consisting of 5 cycles of carboplatin and paclitaxel. Following CRT, patients who were eligible for surgery depending on their pathological response rates underwent surgical resection. Results: Overall survival and progression-free survival were found to be statistically significantly higher in the surgical group (P = .03 and P = .01). Overall survival (P = .001) and progression-free survival (P = .001) were significantly higher in patients with pathological yp-Stage 0–1 compared to those with higher pathological stages. Conclusion: This study highlights the impact of pathological response rates following NACRT, with or without surgery, on treatment outcomes in esophageal cancer. Cite this article as: Çepni K, Uçgun TH, Şam Özdemir M, Aydın SN, Çepni B, Kızıltan HS. Impact of response rates on overall survival following chemoradiotherapy with or without surgery in esophageal cancer. Cerrahpaşa Med J 2026, 50, 0079, doi:10.5152/cjm.2026.25079.